Landcover and crop type classification with intra-annual times series of sentinel-2 and machine learning at central Portugal - Sequeira, Itzá Alejandra Hernández (2020)
Dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geospatial Technologies